2014
DOI: 10.1249/mss.0b013e3182a0595f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Self-reported versus Accelerometer-Measured Physical Activity

Abstract: The participants report through IPAQ-Short Form more vigorous PA and less sedentary time compared with the accelerometer. The difference between self-reported and accelerometer-measured MVPA increased with higher activity and intensity levels. Associations between the methods were affected by sex, age, and education, but not body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
470
11
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(554 citation statements)
references
References 32 publications
58
470
11
15
Order By: Relevance
“…The inconsistencies between the 2 studies are likely attributable to the use of self-reported versus objectively measured physical activity. Differences between selfreported and objectively measured PA, 34,35 as well as self-reported and objectively measured sedentary activities, 36 have been previously reported. Similarly, the proportion of engagement in MVPA for 60 minutes per day on at least 5 days a week was substantially higher in the NEXT full sample based on self-report (>34% at any wave) compared with objective measurement (<10% in the current study), indicating gross overestimation of PA that would be expected to introduce biased estimates of associations with covariates.…”
Section: Discussionmentioning
confidence: 65%
“…The inconsistencies between the 2 studies are likely attributable to the use of self-reported versus objectively measured physical activity. Differences between selfreported and objectively measured PA, 34,35 as well as self-reported and objectively measured sedentary activities, 36 have been previously reported. Similarly, the proportion of engagement in MVPA for 60 minutes per day on at least 5 days a week was substantially higher in the NEXT full sample based on self-report (>34% at any wave) compared with objective measurement (<10% in the current study), indicating gross overestimation of PA that would be expected to introduce biased estimates of associations with covariates.…”
Section: Discussionmentioning
confidence: 65%
“…In addition to the PAI, sedentary time/day and moderate + heavy time/day were used as independent variables. Validity of these variables, by correlation of comparable physical activity questionnaires to accelerometer-determined physical activity measures, has only been fair (0.3-0.4), but it has been suggested that this correlation may be as high a validity as can be expected from a short physical activity questionnaire (10,11). PAI scores, sedentary time and moderate + heavy time were divided into sex-specific quintiles, from low (Q1) to highest (Q5), with Q1 as the referent for PAI and moderate + heavy time and Q5 as the referent for sedentary time.…”
Section: Physical Activity Indexmentioning
confidence: 99%
“…Therefore, responses could have been biased by social desirability or participants' tendency to report practicing PA more than they really do. Regarding this later issue, recent studies have shown that individuals indeed tend to indicate that they have engaged in more PA when asked to self-report than when their behavior is evaluated with an objective measure, such as an accelerometer (Dyrstad, Hansen, Holme, & Anderssen, 2014;Slootmaker, Schuit, Chinapaw, Seidell, & van Mechelen, 2009;Tucker, Welk, & Beyler, 2011). Future research should thus consider supplying self-reported measures of PA practice with objective tools, such as accelerometers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%